Study of Avian Species in Relation to Exotic Trees at Ludhiana, Punjab - Kaur, Manpreet; Kumar, Manoj (International Journal of Bio-resource and Stress Management, 2019)
Birds are exclusively sensitive to alterations both in terms of environmental and ecological. Birds have very close association with trees. There is a complicated connection that is present between birds and their living and non- living components. There are number of variables in a habitat such as vegetation cover, foliage height and these variables influence avian abundance and diversity. Exotics refer to the species carried from outside the country. Occurrence of non-native plants has been revealed to decline innate plant richness and communal range. Exotic species have been recently found as the most common agent of evolutionary traps, influencing species diversity. Invading species repress growth of native flora and this ultimately results in the reduction of nesting sites for birds. The present study on avian community structure in relation to exotic trees was conducted at Punjab Agricultural University, Ludhiana (Location I) and Gurpal Nagar, Ludhiana (Location II). Five different exotic trees were selected i.e. Safeda (Eucalyptus tereticornis), Poplar (Populus deltoides), Bottle brush (Callistemon viminalis), Monkey Puzzle (Araucaria araucana),The Silver Oak (Grivillea robusta). A total of 23 species belonging to 11 orders of birds were recorded. Highest species richness (14) was observed on Bottle Brush (Callistemon viminalis). Passeriformes was the dominant order of bird species observed. Common Myna (Acridotheres tristis), Rose-ringed Parakeet (Psittacula krameri), House Crow (Corvus splendens) and Blue Rock Pigeon (Columba livia) were dominant bird species recorded on selectedexotic trees.